Ambiguity Aversion and Asset Prices in Production Economies - Jahan-Parvar, Mohammad R.; Liu, Hening (Review of Financial Studies, 2014)
We examine a production-based asset-pricing model with an unobservable mean growth rate following a two-state Markov chain and with an ambiguity-averse representative agent. Our model requires a low coefficient of relative risk aversion to produce: (i) a high equity premium and volatile equity returns, (ii) a low and smooth risk-free rate, (iii) smooth consumption growth and volatile investment growth, (iv) countercyclical equity premium and market price of risk, (v) conditional heteroscedasticity in returns, and (vi) long-horizon predictability of excess returns.